The tale of Folp and Whiskers - Blyton, Enid; Sylvia Ward (London, Alligator Books, 2001)
Flop and whiskers are bored with eating lettuce and hoppy round their hutch, if only something exciting would happen....
A1 shelf
Keywords: English fiction stories